Предмет: Математика,
автор: milnerr
выполните действия:
а) -5a(a^2-3a-4)=
б) (5b-1)(b^2-5b+1)=
в) (a^3-a^2+a-1)(a+1)=
Ответы
Автор ответа:
0
1) = - 5A^3 + 15A^2 + 20A
2) = 5B^3 - 25B^2 + 5B - B^2 + 5B - 1 = 5B^3 - 26B^2 + 10B - 1
3) = A^4 - A^3 + A^2 - А + A^3 - A^2 + A - 1 = A^4 - 1
2) = 5B^3 - 25B^2 + 5B - B^2 + 5B - 1 = 5B^3 - 26B^2 + 10B - 1
3) = A^4 - A^3 + A^2 - А + A^3 - A^2 + A - 1 = A^4 - 1
Автор ответа:
0
почему у тебя в третьем получилось -2, а не -1?
Автор ответа:
0
Ты прав - сейчас изменила решение, глянь ))
Похожие вопросы
Предмет: Физика,
автор: rita562735
Предмет: Биология,
автор: nazisodi989
Предмет: Математика,
автор: Аноним
Предмет: Обществознание,
автор: Putilovam